2018
DOI: 10.1212/cpj.0000000000000466
|View full text |Cite
|
Sign up to set email alerts
|

Early myoclonus following anoxic brain injury

Abstract: Cortical and subcortical myoclonus are seen in every sixth patient with cardiac arrest and cannot be distinguished using clinical criteria. Either condition may have good functional outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 27 publications
0
19
0
Order By: Relevance
“…Target temperature varied across studies (ESM Table E3). Fifteen studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] were included for clinical examination, 12 for biomarkers [37][38][39][40][41][42][43][44][45][46][47][48], 26 for electrophysiology , and 15 for imaging [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], while 26 studies were included for more than one prognostic modality.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations
“…Target temperature varied across studies (ESM Table E3). Fifteen studies [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] were included for clinical examination, 12 for biomarkers [37][38][39][40][41][42][43][44][45][46][47][48], 26 for electrophysiology , and 15 for imaging [75][76][77][78][79][80][81][82][83][84][85][86][87][88][89], while 26 studies were included for more than one prognostic modality.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Sensitivity and FPR for index tests based on clinical examination, biomarkers, electrophysiology, and imaging are reported in Tables 3,4,5,6,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,…”
Section: Study Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies assessing early myoclonus have found it to be associated with a poor neurologic outcome, but with poor specificity. Survival rates with a good neurologic outcome despite the presence of myoclonus within 72 hours of out‐of‐hospital cardiac arrest have been reported at 9%–16% 19‐22 . It may be that different forms of myoclonus, such as myoclonus status epilepticus, have a worse prognosis than that of more benign forms of myoclonus such as Lance‐Adams syndrome 23 .…”
Section: Clinical Examinationmentioning
confidence: 99%